PENGUATAN PENDIDIKAN KARAKTER RELIGIUS MAHASISWA MELALUI PROGRAM TUTORIAL KEAGAMAAN - Nasrudin, Ega; Fakhruddin, Agus (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2023)
The Strengthening of Character Education is one of the programs that aims to realize the goals of national education. This research focuses on strengthening religious character education through the PAI Tutorial program implemented at the Indonesian Education University. This research uses a descriptive-qualitative approach. Data were collected through observation, interviews, and documentation. Data analysis techniques used include data collection, data reduction, data presentation, and conclusion. The results of this research indicate the process of strengthening character education through the UPI PAI tutorial program for students who are taking PAI courses. The religious characteristics that are most visibly strengthened include faith, piety, tolerance, trustworthiness, and hard work. The process of strengthening character education is carried out through habituation, exemplification, and the internalization of positive values. The problems encountered in the implementation of this program are the insufficient of quality and quantity of tutors and the lack of awareness among participants